A kinematics-based approach for the shear strength of short fibre-reinforced concrete coupling beams. (1st March 2019) - Mihaylov, Boyan
Highlights: Short FRC coupling beams are modelled based on a kinematic model with only two DOFs. The kinematic based-approach captures the effect of key variables on the shear strength. The model provides similar accuracy to complex nonlinear FEM with thousands of DOFs. Steel fibre efficiency decreases with increasing beam aspect ratio and decreasing concrete strength. Abstract: Short coupling beams are susceptible to brittle shear failures that are typically suppressed with dense transverse and/or diagonal reinforcement. To reduce the amount of shear reinforcement and improve the service behavior of the beam, researchers have proposed a solution with steel fiber-reinforced concrete (FRC). However, while this solution is promising, there are no sufficiently simple mechanical models capable of capturing the shear strength and displacement capacity of short FRC coupling beams without diagonal reinforcement. This paper proposes such a model based on first principles: kinematics, equilibrium, and constitutive relationships for the mechanisms of shear resistance. The model accounts in an explicit manner for five shear mechanisms across the critical shear cracks: diagonal compression in the critical loading zones, aggregate interlock, tension in the stirrups and in the steel fibres, and dowel action of the longitudinal reinforcement. These mechanisms are predicted and the results are compared to 20 tests from the literature as well as to FEM predictions. It is shown that the proposed approach models well the effect of beam aspect ratio, concrete strength, stirrup ratio, and amount of steel fibres. Furthermore, the model is used to develop relationships outlining the effectiveness of steel fibres to reduce conventional stirrup reinforcement in coupling beams with various properties.